Hearing healthcare for workers with hearing loss: audiologists' experiences and views. Issue 25 (4th December 2022) - Zuriekat, Margaret; Semeraro, Hannah; Watson, Victoria; Rowan, Daniel; Kirby, Sarah
Abstract: Purpose: This study explored audiologists' perspectives regarding their interactions with workers with hearing loss (WHL). Materials and methods: Semi-structured interviews were conducted with twenty-five audiologists working in the National Health Service (NHS) and independent companies (IC) in the UK and were thematically analysed. Results: The developed themes and sub-themes (shown in parenthesis) are (1) Current practices and routines (Same approach for most patients; Variations between hearing care services; Audiologists' personal experience of hearing loss) (2) Perceived challenges (Non-routine and challenging cases; The role of hearing technology; Concerns about lack of awareness and knowledge; Communication difficulties between services, Limited funding and resources) (3) Scope for better support (Would like to be informed; Other potential service improvements). Conclusions: This study revealed that audiologists' perceived deficiencies in the hearing rehabilitation for WHL and identified ways to improve it. Key priorities for improvement were found to include addressing audiologists' informational and training needs, facilitating WHLs' access to appointments, improving communication between services, raising awareness in the workplace, developing relevant resources and extending funding for provision of longer appointments and hearing technologies. This is the first time this information has been reported in the literature. Opportunities for conducting further research in this area are suggested. Implications for rehabilitation: Workers with hearing loss face many challenges in work life and have the option of audiologic rehabilitation to alleviate their difficulties and improve their wellbeing; however, this study suggests that workers' audiological care needs improvements. Audiologists should assess and consider patients' work needs and psychosocial concerns in consultations to provide personalised care. Audiology educational programmes, services, and the healthcare system can assist audiologists in helping workers with hearing loss by providing updated knowledge, continuous training and improved interprofessional communication and patients' access to useful resources.